Proyecto de factibilidad para la creación de una empresa que brinde el servicio de monitoreo, rastreo y asistencia usando un llavero localizador portátil S. O. S. en la ciudad de Loja - Villa León, Diego Patricio (2015)
The present investigation was developed in the city of Loja, County of Loja, having as main objective the study of feasibility for the creation of a company that offers the monitoreo service, rakes and attendance using a key ring portable localizer S.Or.S. in the city of Loja With this purpose the analysis was made based on such methods as the inductive, deductive, descriptive, analytic, statistical and the application of technical from investigation like the direct observation and the application of surveys to a sample of 382 potential clients in the city of Loja. Through the market study he/she was proven that an effective demand of monitoreo service exists, I rake and attendance digital mediating portable key ring for the year of study of the project of 65.901 plaintiffs. It was also determined that in the city of Loja companies producers of service don't exist, for what the analysis of the offer was carried out it from the commercialization point of view, being determined that for the year of study the offer is of 4.500 services; the comparison of this figures allowed to determine the unsatisfied demand of 61.401 The installed capacity of the plant is of 1.200 monitoreo services, I rake and attendance using a key ring portable localizer; it calculates that it represents 1,95% of the unsatisfied demand. For the first year of operation he/she will begin with a capacity of 75%, and starting from the second year 5% was increased. The plant will be located in the city of Loja, place where commercial great activity exists, lending the most favorable conditions for the project, the specific location is the streets Av. May 24 and Miguel Riofrío. The setting in march of the project demands of 9 employees between operative and administrative, for that that the creation of the company of monitoreo service, I rake and attendance digital mediating portable key ring will contribute to diminish the unemployment rate in the area. The company will be constituted under the modality of limited Company and its social reason is FALCOM MONITORING SYSTEM CIA. LTDA. The necessary investment for the setting in march of the project is of 37.240,57; of this total 46,30% that corresponds $ 17.240,57 will be contributed by the partners and 53,70 remaining% it will be financed by means of a credit in the Bank of Guayaquil, with an I mount of 20.000 dollars. You prevé that for the first year of operation the company reports an utility of $24414,70 and for the fifth year it ascends at $33843,64 The financial evaluation threw the following results: The Current Net Value of the present project is positive, what means that the value of the company will have an increment of 47578,46 therefore according to this variable the project is accepted. The Internal Rate of Return of the present project is therefore from 55,28 figure superior to the capital cost that is of 15%, according to the evaluation approaches the project it is feasible. The invested capital recovers in 2 years, 2 months and 17 days, inferior time to the lifespan of the project that is of 5 years, therefore you concludes that the project is feasible. The company supports until an increment in its costs of until 4,34% or a decrease of its revenues until 3,78%. Based on the favorable results in all the phases of the study of feasibility you concludes that the project will generate economic benefits to its investors like the society in general, therefore it is feasible its execution